2019
DOI: 10.1017/s0950268819001857
|View full text |Cite
|
Sign up to set email alerts
|

Strategic investment in tuberculosis control in the Republic of Bulgaria

Abstract: As Bulgaria transitions away from Global Fund grant, robust estimates of the comparative impact of the various response strategies under consideration are needed to ensure sustained effectiveness of the tuberculosis (TB) programme. We tailored an established mathematical model for TB control to the epidemic in Bulgaria to project the likely outcomes of seven intervention scenarios. Under existing programmatic conditions projected forward, the country's targets for achieving TB elimination in the coming decades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Screening is the systematic identification of people at risk for TB disease, in a predetermined target group, by assessing symptoms and using tests, examinations or other procedures that can be applied rapidly ( 3 ). Screening can help health providers understand the TB burden in a population ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
“…Screening is the systematic identification of people at risk for TB disease, in a predetermined target group, by assessing symptoms and using tests, examinations or other procedures that can be applied rapidly ( 3 ). Screening can help health providers understand the TB burden in a population ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the second study, Doan and colleagues [ 23 ] evaluated the health and economic outcomes of seven intervention scenarios including switching to a short course regimen for multi-drug resistant TB (MDR-TB), transitioning from inpatient to ambulatory care, and providing food vouchers for patients undergoing TB treatment (a non-medical intervention). This study was conducted from the healthcare payer perspective and predicted outcomes over a 20-year time horizon.…”
Section: Resultsmentioning
confidence: 99%
“…In the two Canadian studies, dynamic transmission modeling was used to establish TB prevalence and smoking habits in the population to inform the decision analysis using a Markov model [ 22 , 24 ]. Doan and colleagues [ 23 ] used a dynamic transmission model that simulated the Bulgarian population’s risk of infection, progression, and transmission of TB over the analytic time horizon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommendations from these three countries are regionally relevant, and provide for more robust evidence to encourage national governments within the region to expedite the examination of barriers delaying the adoption of ambulatory DR-TB care towards more efficient and effective treatment modes. Similarly, another study in Bulgaria showed that while it would not affect TB burden, switching to ambulatory care for eligible TB patients would be markedly cost-saving [ 32 ].…”
Section: Discussionmentioning
confidence: 99%